New combination in the genus Hohenbuehelia (Pleurotaceae) - Vlasenko, Vyacheslav A.; Turmunkh, Dejidmaa; Vlasenko, Anastasia V. (Phytotaxa, 2022)
We studied the type specimens of Pleurotus komarnitzkyi to clarify its taxonomic status. Unlike other species in this genus which grow on wood, P. komarnitzkyi is ecologically distinct as it grows at the base of woody stems of desert herbaceous plants. In addition, its fruiting bodies are small in size, which is not typical for the Pleurotus species. Substrate preferences and morphology of fruiting bodies of P. komarnitzkyi resemble those of Hohenbuehelia species. Based on an analysis of ITS and LSU nrDNA sequences, we propose a new combination in the genus Hohenbuehelia.